Reflection of nursing practice on adverse events in the Neonatal Intensive Care Unit (Research, Society and Development, 2022)
Objective: to reflect on the assumptions of clinical care on the occurrence of adverse events in the midst of neonatal nursing practice. Methodology: This is a reflective theoretical essay, based on clinical care on the occurrence of adverse events in the midst of neonatal nursing practice. Data analysis was organized into two reflexive axes: Adverse events: what they are and their impacts on neonatology; Clinical nursing care in the face of adverse events in neonatology. Results: The provision of care to critically ill patients, in the midst of handling highly complex equipment, requires professional knowledge and technical skills to intervene in the face of changes in their clinical status. Considering that they are essential elements for clinical care in nursing and health, necessary for the practice of nurses in their context of work. Conclusion: Reflecting on clinical care in the event of adverse events in the midst of neonatal nursing practice allows professionals to evaluate their actions, minimizing avoidable risks and injuries.